A Study on Tumor-Infiltrating Lymphocytes in Different Subtypes of Breast Cancer - Polina Dimitrova; Savelina Popovska; Ivan Ivanov (Journal of Biomedical & Clinical Research, 2021)
The study aimed to investigate immune cell infiltration in different subtypes of breast cancer (BC). Retrospectively were selected 100 patients with primary BC, grouped into four molecular surrogate subtypes (Luminal A and Luminal B-like, HER2-positive and triple-negative - TN), determined by immunohistochemistry (IHC). In each patient, a percentage of stromal tumor-infiltrating lymphocytes (TILs) was determined by hematoxylin-eosin staining. IHC was performed using primary antibodies CD3, CD4, CD8, CD20, and FOXP3. Immunophenotyped lymphocytes were counted (separately intratumoral and stromal) and semi-quantitatively graded. In the studied tumors, 10% were defined as lymphocyte-predominant BC. A high count of intratumoral and stromal TILs subsets was found mainly in TN and HER2-positive BC. The stroma is the preferred localization for immune cells in all four BC subtypes. CD3+ T predominates over CD20+ B lymphocytes, with CD8+ T cytotoxic and FoxP3+ T regulatory cells dominating T subtypes. HER2 and TN are more immunogenic than Luminal A and Luminal B – like subtypes of BC. The T-cells’ immune response was predominant in the studied cases of BC, with a predominance of CD8+ Tc and Foxp3+ Treg cells located mainly in the stroma.